ANÁLISES DE DURABILIDADE DE BLOCOS DE SOLO-CIMENTO COM RESÍDUOS INCORPORADOS - Bessa, Sofia; Mello, Tiago; Belo, Bárbara (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Civil construction is one of the most relevant sectors in Brazilian economic scenario. However, it also affects negatively the environment in consequence of its large waste generation. Around 60% of all the solid waste produced in Brazil comes from the construction and demolition activities, which represents about 45 million tons of construction and demolition waste (CDW) per year. Recycling this material is a sustainable alternative to minimize those impacts. The main purpose of this paper is to compare and analyze the mechanical performance and the durability of soil-cement specimens with CDW incorporated, aiming at the verification of the viability of its use in monolithic walls with no structural function. Therefore, 40 specimens were studied in absorption, compression and durability tests according to NBR 13553. All the results overcame Brazilian standards minimum recommendations. The technical viability of the material and the compatibility of CDW with soil was verified. Besides the certified security of the use of CDW soil-cement, its application reinforces the benefits of constructive solutions with low economic and environmental impact.